2023
DOI: 10.1021/acsami.2c22818
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Roles of Trace Fe and F Co-doped into High-Ni Li-Rich Layered Oxides in Performance Improvement

Abstract: High-Ni Li-rich layered oxides (HNLOs) derived from Li-rich Mn-based layered oxides (LRMLOs) can effectively mitigate the voltage decay of LRMLOs but normally suffered from decreased capacity and cycling stability. Herein, an effective, simple, and up-scalable co-doping strategy of trace Fe and F ions via a facile expanded graphite template-sacrificed approach was proposed for improving the performance of HNLOs. The trace Fe and F codoping can far more effectively improve both its rate capability and cycling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The Mn 2p 3/2 peak further splits into two characteristic bands corresponding to Mn 4+ with a binding energy of 642.9 eV and Mn 3+ with a binding energy of 642.2 eV. 37,38 A closer look reveals that the difference in the Mn 2p XPS spectra of the LNM and LTP-LNM materials is negligible, suggesting that the LTP modification exhibits little impact on the structure of the Li 2 MnO 3 domain (C2/m space group). In contrast, a significant variation in the Ni 2p XPS spectra of the materials was observed (Figure 3c).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The Mn 2p 3/2 peak further splits into two characteristic bands corresponding to Mn 4+ with a binding energy of 642.9 eV and Mn 3+ with a binding energy of 642.2 eV. 37,38 A closer look reveals that the difference in the Mn 2p XPS spectra of the LNM and LTP-LNM materials is negligible, suggesting that the LTP modification exhibits little impact on the structure of the Li 2 MnO 3 domain (C2/m space group). In contrast, a significant variation in the Ni 2p XPS spectra of the materials was observed (Figure 3c).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[18] Based on this mechanism, doping and structural modulation have been explored to mitigate voltage attenuation. [31][32][33][34][35][36][37] The voltage decay of the cathode material can be understood as a failure to maintain the integrity and orderability of the layered structure during high cutoff voltage cycling, including oxygen release, phase transitions, and defects. [38] These factors are not isolated but are intrinsically linked.…”
Section: Voltage Attenuationmentioning
confidence: 99%
“…Li et al found that Fe-doped Ni hydroxide powders experienced an enhanced lithium-ion storage capacity with improved cycling stability and rate capability [7]. A similar study claimed that the replacement of Mn by Fe can effectively activate the redox reactions and improve the ionicelectronic conductivities through increasing the lower oxidation state transition metal ions [8]. Te nontransition metal, manganese has also been shown to provide additional storage capacity and suppress capacity fading by increasing the average valence state of Mn which improves the difusion kinetics during Li insertion/extraction.…”
Section: Introductionmentioning
confidence: 99%